Transformasi Manajemen Pendidikan dalam Meningkatkan Mutu Sekolah di Era Digital: Sebuah Studi Literatur - Muhammad Umar Faruq; Muhammad Husni (CV. Lentera Literasi Indonesia, 2026)
Digital transformation has brought significant changes to various aspects of education, including the management of educational institutions. Educational management is required to adapt to technological advancements in order to improve the effectiveness and efficiency of educational administration. This study aims to examine the transformation of educational management in improving school quality in the digital era through a literature review method. The research data were obtained from various sources, including books, journal articles, and previous studies relevant to the topic. Data analysis was conducted through the collection, review, and synthesis of literature related to the transformation of educational management. The findings indicate that the transformation of educational management plays a crucial role in enhancing school quality through the utilization of digital technology in administration, data management, communication, and decision-making processes. However, its implementation still faces several challenges, such as limited technological infrastructure, insufficient digital competencies among educators, and resistance to change. Therefore, effective leadership support, the improvement of human resource competencies, and the provision of adequate infrastructure are essential to ensure the successful implementation of educational management transformation.